Operations scheduling : with applications in manufacturing and services - Pinedo, Michael; Chao, Xiuli (Boston : Irwin/McGraw-Hill, 1999)
Business
Keywords: Operations scheduling; Manufacturing; Production management; Project scheduling; Job scheduling; Workforce scheduling; System architecture